Lung injury in myocardial infarction-associated cardiogenic shock supported by venoarterial extracorporeal membrane oxygenation: a scoping review - Akram M. Zaaqoq; Michael A. Mazzeffi; Melissa A. Vogelsong; Mark Roeser; Sung-Min Cho (BMC Cardiovascular Disorders)
Abstract Background Acute lung injury and acute respiratory failure are frequent complications of cardiogenic shock and are associated with increased morbidity and mortality. Even with increased use of temporary mechanical circulatory support, such as venoarterial extracorporeal membrane oxygenation (VA-ECMO), acute lung injury related to cardiogenic shock continues to have a determinantal effect on patient outcomes. Objectives To summarize potential mechanisms of acute lung injury described in patients with cardiogenic shock supported by VA-ECMO and determine current knowledge gaps. Methods We searched literature from January 1st, 2010, to December 31st, 2023, using MEDLINE, EMBASE, and Web of Science databases on February 27th, 2024. The search strategy was split into two main domains: (a) cardiogenic shock and ECMO and (b) Acute respiratory failure and ECMO. Results The search yielded 2246 citations. After 743 duplicates were removed, 1465 citations remained. Of these studies, 1456 were excluded based on the exclusion criteria, leaving the final eight studies we included in our scoping review. We identified disruption of the pulmonary blood flow in patients with cardiogenic shock, with cardiac arrest being an extreme form of cardiogenic shock. Placing the patient on VA-ECMO could intensify this process of lung injury. Conclusion Acute lung injury in patients with cardiogenic shock, especially when supported by VA ECMO, is a significant complication that is associated with increased morbidity and mortality. There is a limited understanding of the underlying mechanisms that could represent opportunities for future research to mitigate its development and provide the best approach to protecting and monitoring lung function.